2010
DOI: 10.4314/ajtcam.v6i3.57159
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity study and antipyretic effect of the brown alga t<i>Turbinaria conoides</i> (J. agardh) kuetz.

Abstract: The active principles of brown alga, Turbinaria conoides (J.Agardh) Kuetz. (Sargassaceae) was extracted with n-hexane, cyclohexane, methanol and ethanol-water (1:1) and investigated for acute toxicity and antipyretic activity. Phytochemical analysis of the extracts revealed the presence of steroids, flavonoids and reducing sugars. Acute toxicity study was performed in Wistar rats after administration of extracts orally. No mortality was observed up to the dose of 5g/kg for methanol and ethanol-water (1:1) extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The acute toxicity study was determined in mice as LD50 > 10 g kg -1 , which agrees with other toxicity studies of brown algae such as Sargassum liebmannii and the fucoidan from Saccharina japonica (Kumar et al 2009, Tapia-Martinez et al 2019. According to the value of LD50 in the scale proposed by Loomis & Hayes (1996), M. pyrifera can be classified as non-toxic.…”
Section: Discussionsupporting
confidence: 83%
“…The acute toxicity study was determined in mice as LD50 > 10 g kg -1 , which agrees with other toxicity studies of brown algae such as Sargassum liebmannii and the fucoidan from Saccharina japonica (Kumar et al 2009, Tapia-Martinez et al 2019. According to the value of LD50 in the scale proposed by Loomis & Hayes (1996), M. pyrifera can be classified as non-toxic.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, no behavioral changes, consciousness defects, or comas were seen in the tested animals, thus, indicating that the lethal dose 50 (LD 50 ) of D. dichotoma is significantly high in vivo (well above 5000 mg/kg body weight). Along the same line, the acute toxicity of the brown algae Turbinaria conoides reported that oral ingestion of a dose up to 5 g/kg of methanol and ethanol-water (1 : 1) extracts was highly nontoxic and did not cause single mortality in rats [58].…”
Section: Acute Toxicitymentioning
confidence: 89%
“…Brown alga, Turbinaria conoides have evaluated with n-hexane, cyclohexane, methanol and ethanol-water for acute antipyretic activity study reveals that n-hexane, cyclohexane and ethanol-water extracts caused increase in serum cholesterol, protein and alkaline phosphatase levels and concluded that Cyclohexane extract exhibited more significant antipyretic activity than the other extracts [12].…”
Section: S Sadish Kumar Et Al (2009)mentioning
confidence: 99%
“…It is used as antipyretic [12], Antimicrobial [13], Antidiabetic [15], Antioxidant [17], Hepatoprotective [23], Antifungal [25], antiulcer [27], Antitumor [28], Anticoagulant [37], Antibacterial [40].…”
Section: Usesmentioning
confidence: 99%